The Relationship between Autonomy and Adult Mental Capacity in the Law of England and Wales. (18th April 2018) - Skowron, Paul
Abstract: Judges in England and Wales tell three apparently contradictory stories about the relationship between autonomy and mental capacity. Sometimes, capacity is autonomy's gatekeeper: those with capacity are autonomous, but those without capacity are not. Sometimes, capacity is necessary for autonomy but insufficient; for voluntariness, freedom from undue external influences, is also required. Finally, sometimes autonomy survives incapacity, and a person without capacity is nevertheless treated as autonomous. These three accounts coexist, so no story of evolution, in which one account comes to replace another, can be told. Similarly, no story of judicial factions is plausible, for judges switch account to suit the facts of a particular case. This article gives examples of all three accounts, traces their recent history, and shows how each serves one or two characteristic purposes. It then shows how they can be combined into a coherent descriptive account of the relationship between autonomy and mental capacity in domestic law.